Conversational dominance and gender : a study of Japanese speakers in first and second language contexts - Itakura, Hiroko (Pragmatics & beyond, 2001)
This book investigates the notion of conversational dominance in depth, and seeks to establish a systematic method of analysing it. It also offers a new insight into the role of gender and the pragmatic transfer of conversational norms in the first and second language conversations among native speakers of Japanese. Drawing upon a critical synthesis of insights from several different fields, including Conversation Analysis, the Birmingham school of discourse analysis, and dialogical analysis, the author proposes an innovative analytical framework for operationalising the concept of dominance in.